Workplace Learning debating five critical questions of theory and practice (New directions for adult and continuing education, 1996)
The need for effective training and retraining of American workers is more critical than ever before, but the practice of learning in the workplace lags behind. To inspire improved practice in adult education and human resource development, this volume presents differing perspectives on some of the most important questions confronting those engaged in educating adults in the workplace. Researchers and practitioners shed light on current issues by examining some of the tensions surrounding the practice of adult education and HRD. This is the 72nd issue in the journal series New Directions for Adult and Continuing Education. For more information on the series, please see the Journals and Periodicals page.